SEARCHING KEY TRAITS FOR FURTHER DESCRIPTION OF THER DESCRIPTION OF PHYTOSEIIDAE MITE F AE MITE FAMILY - S. T. PAVANA KUMAR; KRISHNA KARMAKAR; ADAM KAMEI; AND 2 DAVID KAMEI, DEBASIS MAZUMDAR (The Bioscan, 2018)
The predatory mite family, Phytoseiidae is one of the most explored groups worldwide as biological agents against phytophagous mite pests and small insects viz thrips, whiteflies, coccids and pseudo coccids in alternative to application of acracides. In search of key traits of predatory mites for proper identification as the species level classification of Indian phytoseiids is carried out. Our present study considered 171 species along with their 48 morphological characters with MDS. Principal coordinate analysis (PCoA) was carried out using Gower’s similarity index and the key traits were retained upon 10 % relaxation provided in the component score matrix. Larger amount of variance (85.5%) explained by 6 major traits with eigen value >1, while length (0.907) and width of dorsal shield (0.504) contributed major variation. Traits like length and width of dorsal shield setae, length ventrianal shield, Ratio R1/s6, Macro setae SgIV and Length of setae s4 is found responsible for major variance in the classification of Phytoseiidae. The key traits can be utilized as importance tools of classification, pest control and predatory phytoseiid mite. This approach can also helps in identification of new species with no time holistic approach.